2008
DOI: 10.1016/j.cbi.2008.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the solution structure of a neuroligin/β-neurexin complex

Abstract: SUMMARYNeuroligins are postsynaptic cell adhesion molecules that promote synaptic maturation and stabilization upon binding with presynaptic partners, the α-and β-neurexins. Using a combination of analytical ultracentrifugation, small angle x-ray, and neutron scattering, we have characterized the low-resolution three-dimensional structure of the extracellular domain of the neuroligins, free in solution, and in complex with β-neurexin. The globular extracellular domain of the neuroligins forms stable homodimers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…The Tg ChEL domain, for instance, physically associates with I-II-III with an equimolar binding stoichiometry (Fig. 6); identical to that found for neuroligin-1 and its binding partner ␤-neurexin (40). In this report, we found that AChE and secretory neuroligins also can bind to upstream Tg regions I-II-III (Fig.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The Tg ChEL domain, for instance, physically associates with I-II-III with an equimolar binding stoichiometry (Fig. 6); identical to that found for neuroligin-1 and its binding partner ␤-neurexin (40). In this report, we found that AChE and secretory neuroligins also can bind to upstream Tg regions I-II-III (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…3, lower). These data directly implicate the carboxyl-terminal ␣-helices in ChEL dimerization, strongly supporting a 4-helix bundle dimerization mechanism similar to that used by AChE and other cholinesterase-like family members (39,40).…”
Section: Similarity Of the Tg Chel Domain To Other Ache-family Members-supporting
confidence: 59%
See 1 more Smart Citation
“…Up to six alternative splice sites (SS#1–6) accept inserts ( red ). The stalk region between LNS6 and transmembrane region ( TM ) is visualized as rod-like due to massive O- glycosylation ( 119 ). B , binding of αDAG (immunoblots, upper panel ) and Nlgn1 ( middle panel ) from mouse brain was tested by pull-down with Fc-tagged extracellular domain of Nrxn1α carrying an insert in SS#4 ( lane 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…SNTG2 encodes a scaffolding protein which interacts with neuroligins (NL4X and NL4Y) . Mutations of neuroligins (NL3 and NL4X) are implicated in autism and ID . Furthermore, Rosenfeld et al identified by whole‐genome arrays in a cohort of 1461 individuals referred for autism spectrum disorder a patient with a deletion involving a part of SNTG2 .…”
Section: Discussionmentioning
confidence: 99%